Uso de um software de simulação computacional baseado em agentes na modelagem de uma rota de transporte público da cidade de Mossoró-RN - Sousa, Raísa Pereira de (Universidade Federal Rural do Semi-Árido, 2019)
The model of agent-based simulation has been increasingly used over time, not only for its characteristics, but also for the potentialities of its use as the applicability in the different areas. This work aimed to elaborate the urban public transport modeling of a bus line in the city of Mossoró-RN through computational simulation. The tool used in the study was Multi-Agent Transport Simulation (MATSim), an agent-based simulation software that allows the analysis of transport systems based on activity models, available free of charge and which can represent a substantial change in the way transportation systems are analyzed in the future. In order to prove the applicability of the tool to public transport modeling, a MATSim model was built for a bus line in the city of Mossoró-RN. The proposed model can simulate the trips of agents with origin or destination in the region of study. The results of this model were visualized and analyzed through Simundo Via independent visualization software. The results demonstrate that MATSim is a flexible enough tool to serve as a basis for the development of a public transport traffic model in the city of Mossoró.
Monografia
Keywords: Modelagem por agentes; Simulação de transporte público; MATSim; Modeling by agents; Simulation of public transport; MATSim; ENGENHARIAS::ENGENHARIA DE PRODUCAO